Treatment Options for Metastatic Gastric Cancer After Recurrence Following Perioperative FLOT: A Critical Review - Peixoto, Renata DAlpino; Belotto, Marcos; Donadio, Mauro Daniel Spina (Archives of Clinical and Biomedical Research, 2025)
Background: Gastric cancer (GC) recurrence after perioperative FLOT chemotherapy is common, with limited guidance on optimal first-line treatment in the metastatic setting. Despite the survival benefits of FLOT, up to 50% of patients relapse, highlighting the need for effective postrecurrence treatment strategies. Objective: This manuscript reviews treatment options for patients with recurrent GC after perioperative FLOT, focusing on the impact of prior chemotherapy and the role of key biomarkers such as PD-L1, dMMR/ MSI, HER2, and Claudin-18.2. Results: Post-FLOT recurrence poses challenges due to prior exposure to taxanes, platinum agents, and fluoropyrimidines. Irinotecan-based regimens show promise, though data on optimal treatment are scarce. Biomarkers such as PD-L1, dMMR/MSI-H, and Claudin-18.2 guide targeted therapies, but their efficacy in patients previously treated with FLOT remains unclear. Conclusion: The management of recurrent GC after perioperative FLOT is complex and should consider performance status, disease burden, prior treatment tolerance, pathological response to FLOT, and molecular profile. Further research is needed to determine the best therapeutic approaches for this population.